Complexity in Design-Driven Innovation: A case study of knowledge transfer flow in subsea seismic sensor technology and design education - Pavel, Nenad; Berg, Arild (Design and Technology Education: An International Journal, 2015)
To the extent previously claimed, concept exploration is not the key to product innovation. However, companies that are design focused are twice as innovative as those that are not. To study design-driven innovation and its occurrence in design education, two case studies are conducted. The first is an example of design practice which includes observation and cooperation process maps in an offshore project. The second is an example of product design education which includes observations of teamwork, team member interviews and archival studies. While the first case study demonstrates how a company innovates through a design-driven process with complex knowledge transference and systematic planning and improvisation, the second case study shows students managing their design processes through concept generation in a less complex trial and error process. Knowledge exploration as a part of design activity was analyzed through the criteria of network paradoxes. A pedagogic concept has been synthesized and validated internally based on the case study, and externally based on other design practices and design research. The pedagogic concept synthesized was Knowledge Transfer Flow [KTF]. The KTF concept can help to orient design students within the information-saturated design processes integrated within complex innovation systems.